Trends in Functional Programming 15th International Symposium, TFP 2014, Soesterberg, The Netherlands, May 26-28, 2014. Revised Selected Papers - Hage, Jurriaan (Springer, 2015)
This book constitutes the thoroughly refereed revised selected papers of the 15th International Symposium on Trends in Functional Programming, TFP 2014, held in Soesterberg, The Netherlands, in May 2014. The 8 revised full papers included in this volume were carefully and selected from 22 submissions. TFP is an international forum for researchers with interests in all aspects of functional programming, taking a broad view of current and future trends in the area.